Empowering Circular Economy Education Through Student-Led Sustainability Initiatives in Rural Sarawak - Florianna Lendai, Michael Mulok; Lennevey, Kinidi; Helmi, Sumilan; Hana, Hamidi; Victoria, Jonathan (The Italian Association of Chemical Engineering, 2025)
Climate education in rural Malaysian communities is often constrained by poor digital infrastructure and the limited availability of locally relevant examples of sustainability concepts such as the circular economy (CE). The purpose of this study was to evaluate a student-led service-learning programme in Kampung Assum, Sarawak, designed to embed CE education through experiential learning. Guided by Kolb’s learning cycle, three modules were implemented with 24 villagers: upcycling bamboo waste into handmade paper, extracting essential oil from lemongrass, and composting household food waste. Pre- and post-intervention surveys using Likert scales showed knowledge gains of 30–50 percentage points across the modules, with more than 90% of participants reporting increased confidence in applying the new skills. Qualitative reflections further indicated that participants valued hands-on and culturally familiar learning, and many expressed intentions to adopt the practices at home or explore them as potential income-generating opportunities. The findings demonstrate that student-led experiential learning can effectively bridge climate education gaps in rural Malaysia by linking CE concepts to daily livelihoods, while also offering universities a practical model for embedding sustainability education into curricula and enhancing community resilience.